Intensitas Latihan Interval dan Aktivitas Antioksidan Endogen - Muchsin Doewes; Kiyatno Kiyatno (MEDIA MEDIKA INDONESIANA, 2010)
Interval training intensity and endogen antioxidant activityBackground: Physical training increases free radical generation which is balanced by endogenous antioxidant generation e.g. SOD (superoxide dismutase) and GPx (glutathione peroxidase). This later is influenced by intensity, duration, muscle type and age. The aims of this study is to compare the three kinds of interval training intensity in enhancing SOD and GPx activity.Method: An experimental quantitative study with the posttest only control group design was used in this study. Thirty six students of JPOK-FKIP Sebelas Maret University were randomly selected to become the experimental subjects and divided into four groups (1) intensive repetition runing 10x50 m, (2) extensive repetition runing 3x400 m, (3) continuous aerobic training past running 30 minutes, and (4) controlled group. The interval training were treated 3x per week for 8 weeks. At the 8th week SOD and GPx activity were determined by using enzymatic method with Cobas Mira instrument. The t-test with SPSS 13.0 for window program was use for analyzing all collected data with 95% CI.Result: There were significance difference the SOD and GPx activity between extensive repetition group with controlled group (p<0.05).Conclusion: The extensive repetition intensity is the significance for enhancing the enzymatic activity of SOD and GPx to compare with control group, and have the higher level than intensive repetition and continuous aerobic training.ABSTRAKLatar belakang: Latihan fisik meningkatkan pembentukan radikal bebas yang diimbangi peningkatan pembentukan antioksidan endogen seperti SOD (superoxide dismutase) dan GPx (glutathione peroxidase). Pembentukan antioksidan SOD dan GPx dipengaruhi oleh intensitas latihan, durasi, jenis otot yang dilatih dan umur. Tujuan penelitian ini untuk membandingkan tiga kelompok intensitas latihan interval yang meningkatkan aktivitas enzim SOD dan GPx.Metode: Jenis penelitian kuantitatif–eksperimental menggunakan rancangan penelitian the posttest only control group design. Subyek penelitian diambil secara acak sederhana (n=36), dibagi menjadi 4 kelompok (1). K1: intensive repetition lari 10x50 m, (2). K2: extensive repetition lari 3x400 m, (3). K3: continuous aerobic training lari cepat 30 menit; (4). K4: kelompok kontrol. Latihan interval dilakukan 3 kali/minggu dilakukan berkesinambungan selama 8 minggu berturut-turut. Pada minggu ke delapan diambil 5 mL darah untuk diperiksa aktivitas SOD dan GPx menggunakan metode enzimatik dengan alat Cobas Mira. Analisis data dengan uji t menggunakan program komputer SPSS 13.0 for Window dengan tingkat kepercayaan 95%.Hasil: Terjadi perbedaan bermakna kadar SOD dan GPx pada extensive repetition dengan kelompok kontrol (p<0,05).Simpulan: Aktivitas enzim SOD dan GPx paling tinggi pada latihan interval extensive repetition dibanding intensive repetition dan continuous aerobic training, dan berbeda bermakna dengan kelompok kontrol.